PROSES DAN ANALISIS TEKANAN KONDENSOR PENYULINGAN DAUN CENGKEH - Dzikrulloh, Farkhaz rizky (Universitas Majalengka, 2021)
Job Training Report at the Cakra Buana HOME INDUSTRY. Majalengka: Process and Pressure Analysis of Clove Leaves Distillation Condenser. Mechanical Engineering Study Program, Faculty of Engineering, Majalengka University. Job Training is a student program in developing their abilities and qualities in the world of work. The practitioner chooses a placement in a clove oil refinery to determine the beginning of the refining process and the end of the process and performs an analysis of the pressure entering the condenser. The refining process is a method of separating water and steam from heating clove leaves. In distillation, the mixture of water vapor and clove leaf oil vapor is cooled into a liquid form and the results from the distillation of oil and water are separated.Job Training Report at the Cakra Buana HOME INDUSTRY. Majalengka: Process and Pressure Analysis of Clove Leaves Distillation Condenser. Mechanical Engineering Study Program, Faculty of Engineering, Majalengka University. Job Training is a student program in developing their abilities and qualities in the world of work. The practitioner chooses a placement in a clove oil refinery to determine the beginning of the refining process and the end of the process and performs an analysis of the pressure entering the condenser. The refining process is a method of separating water and steam from heating clove leaves. In distillation, the mixture of water vapor and clove leaf oil vapor is cooled into a liquid form and the results from the distillation of oil and water are separated.